DELAYED DIAGNOSIS OF LYMPHOCYTIC HYPOPHYSITIS PRESENTING AS CHRONIC HEADACHES: A CASE REPORT - Ismail, Ihsan; Zuki, Rabeah Md; Mukhtar, Murshidah Ainun (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Lymphocytic hypophysitis (LH) is a rare autoimmune inflammatory disorder of the pituitary gland, often presen- ting with non-specific symptoms leading to diagnostic delays. This case highlights the challenges in the timely diagnosis of LH and the consequences of treatment default in a young male. CASE A 37-year-old male with a three-year history of chronic headaches, initially managed symptomatically, presented with recurrent episodes of worsening headaches, vomiting, and chest pain requiring multiple emergency department visits over two years. After 2 years of intermittent visits, a non-contrast computed tomography (CT) brain, performed due to persistent and escalating headaches, revealed a possible pituitary fossa mass. Subsequent urgent magnetic resonance imaging (MRI) confirmed a bulky pituitary gland with minimal suprasellar extension. Hormonal evaluation revealed panhypopituitarism. Based on clinical and radio- logical findings, a diagnosis of lymphocytic hypophysitis was suspected. The patient was commenced on hydrocor- tisone and thyroid hormone replacement. Regrettably, the patient defaulted on follow-up and discontinued his prescribed medications in favour of traditional treatment. This case underscores the insidious presentation of LH, where chronic headaches can be the predominant initial symptom, leading to significant delays in diagnosis. The patient’s repeated emergency department visits for non- specific symptoms highlight the need for a high index of suspicion for underlying endocrine disorders in patients with persistent and evolving complaints. The eventual radiological findings of a pituitary mass and subsequent confirmation of panhypopituitarism were crucial for sus- pecting LH. The patient’s decision to discontinue conven- tional treatment and opt for traditional remedies emphasizes the importance of patient education, adherence strategies, and culturally sensitive approaches in managing chronic endocrine conditions. The potential long-term sequelae of untreated panhypopituitarism warrants concern. CONCLUSION This case serves as a reminder of the diverse clinical mani-festations of lymphocytic hypophysitis and the importance of considering pituitary pathology in patients with chronic headaches. Early radiological investigation in cases of persistent or worsening headaches, coupled with hormonal evaluation, is crucial for timely diagnosis and management. Furthermore, addressing factors influencing treatment adherence, including patient beliefs and prefe- rences, is essential for optimal outcomes in chronic endocrine disorders.